Competitive interactions among multiple non‐native salmonids and two populations of Atlantic salmon. Issue 1 (21st January 2014) - Houde, Aimee Lee S.; Wilson, Chris C.; Neff, Bryan D.
Abstract Competitive interactions with non‐native species can have negative impacts on the conservation of native species, resulting in chronic stress and reduced survival. Here, juvenile Atlantic salmon (Salmo salar) from two allopatric populations (Sebago and LaHave) that are being used for reintroduction into Lake Ontario were placed into semi‐natural stream tanks with four non‐native salmonid competitors that are established in Ontario streams: brown trout (S. trutta), rainbow trout (Oncorhynchus mykiss), Chinook salmon (O. tshawytscha) and coho salmon (O. kisutch). Brown trout and rainbow trout reduced the survival and fitness‐related traits of Atlantic salmon, whereas Chinook salmon and coho salmon had no impact on these traits. These data support theories on ecological niche overlap and link differences in observed aggression levels with competitive outcomes. Measurements of circulating hormones indicated that the Atlantic salmon were not chronically stressed nor had a change in social status at the 10‐month time point in the semi‐natural stream tanks. Additionally, the Sebago population was better able to coexist with the non‐native salmonids than the LaHave population. Certain populations of Atlantic salmon may thus be more suitable for some environments of the juvenile stream phase for the reintroduction into Lake Ontario.